Trends and socioeconomic differences in policy triggers for thinking about quitting smoking: Findings from the International Tobacco Control (ITC) Europe Surveys. (1st October 2015) - Hummel, Karin; Nagelhout, Gera E.; Willemsen, Marc C.; Driezen, Pete; Springvloet, Linda; Mons, Ute; Kunst, Anton E.; Guignard, Romain; Allwright, Shane; van den Putte, Bas; Hoving, Ciska; Fong, Geoffrey T.; et al.
Highlights: We investigated 4 policy triggers for thinking about quitting smoking. We examined trends and socioeconomic differences in mentioning triggers. Cigarette price was the most common reported trigger to think about quitting. All triggers were mentioned more often by low/moderate than high socioeconomic status (SES) smokers. SES differences did not change significantly over time for most policy triggers. Abstract: Introduction: The aim of the current study is to investigate trends and socioeconomic differences in policy triggers for thinking about quitting in six European countries. Methods: Data were derived from all available survey waves of the International Tobacco Control (ITC) Europe Surveys (2003–2013). France conducted three survey waves ( n  = 1420–1735), Germany three waves ( n  = 515–1515), The Netherlands seven waves ( n  = 1420–1668), Ireland three waves ( n  = 582–1071), Scotland two waves ( n  = 461–507), and the rest of the United Kingdom conducted seven survey waves ( n  = 861–1737). Smokers were asked whether four different policies (cigarette price, smoking restrictions in public places, free or lower cost medication, and warning labels on cigarette packs) influenced them to think about quitting. Generalized Estimating Equation (GEE) models were estimated for each country. Results: Cigarette price was mentioned most often in all countries and across all waves as trigger for thinking about quitting. Mentioning cigarette price and warning labels increased after the implementation of price increases and warning labels in some countries, while mentioning smoking restrictions decreased after their implementation in four countries. All studied policy triggers were mentioned more often by smokers with low and/or moderate education and income than smokers with high education and income. The education and income differences did not change significantly over time for most policies and in most countries. Conclusions: Tobacco control policies work as a trigger to increase thoughts about quitting, particularly in smokers with low education and low income and therefore have the potential to reduce health inequalities in smoking.